2010
DOI: 10.1586/eri.10.90
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive therapy for cerebral malaria and other severe forms ofPlasmodium falciparummalaria

Abstract: Severe malaria due to Plasmodium falciparum causes more than 800,000 deaths every year. Primary therapy with quinine or artesunate is generally effective in controlling P. falciparum parasitemia, but mortality from cerebral malaria and other forms of severe malaria remains unacceptably high. Longterm cognitive impairment is also common in children with cerebral malaria. Of the numerous adjunctive therapies for cerebral malaria and severe malaria studied over the past five decades, only one (albumin) was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
0
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 82 publications
(82 reference statements)
1
95
0
5
Order By: Relevance
“…Nanostructured lipid carrier [32] and lipid nanoparticles [61] of artemether have shown improved antimalarial activity in P. berghei model. Peter's four-day suppressive test was performed on AAN at two dose levels viz, 100 and 50% of therapeutic dose of the drug using P. berghei-infected Swiss albino mice.…”
Section: In Vivo Antimalarial Efficacy In P Berghei Infected Micementioning
confidence: 99%
“…Nanostructured lipid carrier [32] and lipid nanoparticles [61] of artemether have shown improved antimalarial activity in P. berghei model. Peter's four-day suppressive test was performed on AAN at two dose levels viz, 100 and 50% of therapeutic dose of the drug using P. berghei-infected Swiss albino mice.…”
Section: In Vivo Antimalarial Efficacy In P Berghei Infected Micementioning
confidence: 99%
“…Further experiments are required to identify which receptors are recognized by P. berghei parasites and discern the specific parasite stages of the intraerythrocytic cycle that bind. Ultimately, this could reveal how parasites use cytoadherence to evade the immune system inside the host, how they contribute to the severity of disease, and how therapies work at interfering with this binding to lessen the global burden of CM (91,92).…”
Section: Discussionmentioning
confidence: 99%
“…However no single adjunct therapy has yet shown clear efficacy in improving the outcome of treatment of cerebral malaria. 6 There is hope that vitamin A may be of use as in vitro studies have shown that retinol levels corresponding to normal serum levels can suppress growth of Plasmodium falciparum 7 while community based studies have shown significant reduction in malaria episodes in children in whom vitamin A was supplemented. 8 The real immunogenic mechanisms of action of vitamin A is not yet clear.…”
Section: Introductionmentioning
confidence: 99%